Long‐T2‐suppressed zero echo time imaging with weighted echo subtraction and gradient error correction. Issue 2 (10th September 2019) - Lee, Hyo Min; Weiger, Markus; Giehr, Caspar; Froidevaux, Romain; Brunner, David Otto; Rösler, Manuela Barbara; Pruessmann, Klaas Paul
Abstract : Purpose: To perform direct, selective MRI of short‐T2 tissues using zero echo time (ZTE) imaging with weighted echo subtraction (WSUB). Methods: Radial imaging was performed at 7T, acquiring both ZTE and gradient echo (GRE) signals created by bipolar gradients. Long‐T2 suppression was achieved by weighted subtraction of ZTE and GRE images. Special attention was given to imperfections of gradient dynamics, to which radial GRE imaging is particularly susceptible. To compensate for gradient errors, matching of gradient history was combined with data correction based on trajectory measurement. The proposed approach was first validated in phantom experiments and then demonstrated in musculoskeletal (MSK) imaging. Results: Trajectory analysis and phantom imaging demonstrated that gradient imperfections were successfully addressed. Gradient history matching enabled consistency between antiparallel projections as required for deriving zeroth‐order eddy current dynamics. Trajectory measurement provided individual echo times per projection that showed considerable variation between gradient directions. In in vivo imaging of knee, ankle, and tibia, the proposed approach enabled high‐resolution 3D depiction of bone, tendons, and ligaments. Distinct contrast of these structures indicates excellent selectivity of long‐T2 suppression. Clarity of depiction also confirmed sufficient SNR of short‐T2 tissues, achieved by high baseline sensitivity at 7T combined with high SNR efficiency of ZTE acquisition. Conclusion: Weighted subtraction of ZTE and GRE data reconciles robust long‐T2 suppression with fastest k‐space coverage and high SNR efficiency. This approach enables high‐resolution imaging with excellent selectivity to short‐T2 tissues, which are of major interest in MSK and neuroimaging applications.